Multiple paternity in Asian black bear Ursus thibetanus (Ursidae, Carnivora) determined by microsatellite analysis - Yamamoto, Toshiaki; Tamatani, Hiroo; Tanaka, Junpei; Kamiike, Kumiko; Yokoyama, Shotaro; Koyama, Masaru; Kajiwara, Mayuka (Mammalia (Paris), 2013)
We performed microsatellite paternity analyses of two Asian black bear littermates with a known mother. Using Cervus 3.0, we identified the probable father among 17 candidate fathers for Cub 1, but failed to identify a probable father for Cub 2. Cub 1 and her probable father shared at least one allele at all 13 loci. In contrast, Cub 2 and the probable father of Cub 1 had mismatching alleles at eight loci, indicating that the two cubs are offspring of different fathers. This is probably the first evidence for multiple paternity in Asian black bears.